Democratising Afghanistan: an analysis of the 2005 parliamentary elections - Sahibuddin, Wahabuddin (IIUM Press, 2006)
The interviews and observation of the September 2005 elections for the lower house of parliament and provincial councils in Afghanistan disclose that despite shortcomings, the elections were relatively free. The elections, conducted in the absence of party politics, created a divided legislature struggling to unite. Women members, equally divided by region and ethnicity, may exert a moderating influence on the legislature, which is dominated by the "Islamist right."